Parental responses to increasing levels of handicapping in a burying beetle. (23rd September 2019) - Ratz, Tom; Nichol, Thomas W; Smiseth, Per T
Abstract: Parental care is highly variable, reflecting that parents make flexible decisions about how much care to provide in response to variation in the cost and/or benefit of care. Handicapping has traditionally been used as a tool for increasing the energetic cost of care, thereby inducing a reduction in care by handicapped parents. However, recent evidence shows that handicapped parents sometimes provide more care, suggesting that handicapping can trigger terminal investment. Here, we investigate responses to different levels of handicapping in the burying beetle Nicrophorus vespilloides by comparing handicapped female parents fitted with a wide range of handicaps, as well as control females without a handicap. We found that handicapped females spent more time provisioning food and less time being absent from the crypt than control females, while there was no effect of the level of handicapping among handicapped females. We found no effect of handicapping on larval begging behavior, larval performance (mean larval mass and brood size at dispersal), or female investment in future reproduction (i.e., weight gain while breeding and life span after breeding). Our findings provide no support for the widely held assumption that handicapping simply increases the cost of care. Instead, our results are consistent with the suggestion that handicapping triggers terminal investment by suppressing the condition of parents below the threshold at which terminal investment is triggered. Lay Summary: Parents adjust their time spent caring for their offspring to balance the benefit to their offspring and the cost to themselves. To study parental decisions, we handicapped female parents of the burying beetle Nicrophorus vespilloides . We find that handicapped parents provide more care to their current brood, contrasting with prior work showing that handicapped parents provide less care. Our results suggest that, when parents are physically impaired, they shift their investment towards current reproduction.